An assessment of the implementation of the hazard analysis critical control point system (HACCP) in the tuna canneries in General Santos City - Baltazar-Reyes, Hazel Marie L.; Rañeses, Nestor (Quezon City University of the Philippines Diliman, 2005)
Food safety has been receiving increasing attention around the globe. Who would ever forget the tragedy that hit Jack in the Box-one of the largest hamburger chains in the United States? Probably the most unprecedented case of food poisoning in the US, the incident undoubtedly brought about increased awareness on food safety, not only in the United States but also around the globe. On January 15, 1993, about 400 cases of food poisoning cases were linked to undercooked beef at the Jack in the Box restaurants in the Pacific Northwest. In a span of a month, three toddlers died of E. coli 0157:H7 poisoning, the strain of which was linked to Jack in the Box. Terry Herrick, owner of two Jack in the Box outlets in the area related that just a few days after the first child died, his Agoura outlet had emptied out and by the end of that week, sales were down by 80 percent. There were no customers in Seattle. No one ever imagined how a mere shortcoming in the cooking process could take the life of 3 innocent children, inflict illness to a humongous number of people, and lead the fifth largest hamburger chain the United States close to extinction. But how did Jack in the Box respond to such crisis and manage to redeem itself and be considered the leader in food safety in the US fastfood industry? After its initial attempts of evading responsibility and partially blaming its suppliers and state health officials until the crisis was nearly a week old, Jack in the Box suspended their hamburger sales, recalled meat from distributors, increased cooking times and temperatures, and pledged to pay all medical costs related to the fateful incident. Jack in the Box also hired a prominent food safety consultant in the person of Dr. David Theo to become a vice president of quality assurance and product safety. Dr. Theo began to build the fastfood industry's first Hazard Analysis Critical Control Points (HACCP) program, a program that brought dramatic changes on how people in Jack in the Box do things to ensure that their consumers not only get what they want, but also what they are most entitled to their right to safe food. HACCP is a systematic approach to food safety, involving the analysis and control of hazards that may potentially occur in the entire food production system. It is built on robust pre-requisites such as Good Manufacturing Practices (GMP), Good Agricultural Practices, or in the case of the fishery sector, Good Architecture Practices (GAP), and the Standard Sanitation Operating Procedures (SSOP). The primary motivation for the study is the increasing popularity of the HACCP as the most effective way to ensuring food safety. In 1997, HACCP became a mandatory regulation for the export of fish and seafood products in countries like the United States of America (USA), Canada, Australia and other countries in the European Union (EU). HACCP became a ticket to seafood export trade - "No HACCP certification, No Export." Thus, to be able to enter, retain and expand their market access, processors and exporters of fish and seafood products were left with no other choice but to adapt the HACCP into their production operations. The results of the study were expected to provide useful information on how food processors, particularly seafood processors who are eyeing the export market but are not yet HACCP certified, can work towards HACCP compliance and ultimately, HACCP certification and gain access to the international market. At the national level, the output of the study could aid the government, the academe and the Philippine food industry in the development of more appropriate strategies for better and faster adoption and implementation of HACCP in the Philippines.
Canned tuna, being one of the Philippine's top agri-food exports, was chosen as the primary subject of the project study. Currently, there are eight tuna canneries in the country : six are located in General Santos City while the other two are located in Zamboanga City. All of the eight tuna canneries are already HACCP certified. However, the scope of the study was limited to the six tuna canneries in General Santos City. The project study primarily aimed at assessing the current implementation of HACCP in the tuna canneries in General Santos City. The specific objectives of the study included gaining insights on the canned tuna industry's experiences on HACCP implementation, gaining insights on how the Philippine government currently implements the HACCP in the fisheries sector and developing strategies and recommendations for the effective implementation of HACCP at the firm and national levels. The cost of HACCP implementation is outside the scope of this study and can therefore be a subject for further investigation. The methodology used to gather data included internet and library researches, participation in the Philippine Association of Food Technologists, Inc.'s annual convention, interviews with a key resource person from the Bureau of Fisheries and Aquatic Resources as well as plant managers, supervisors, and line leaders from 5 out of 6 tuna canneries in General Santos City and plant visits. However, only 4 out of the 6 canneries agreed to the plant visit. From the review of literature, it was gathered that tuna is the world's 3rd main fish catch and that in the Philippines, tuna is a big business. The center for tuna production in the Philippines is located in General Santos City, where 6 out of the 8 tuna canneries in the country are located. Philippine tuna is exported to countries like the United States and Canada, as well as countries in the European Union, mainly in canned form. Canned tuna comprised almost 60 percent of tuna exports in 2002, 45 percent of which went to the US and EU markets. Around 9 percent of the canned tuna produced locally are sold overseas and the remaining 5 percent goes into the domestic market. The Philippine canned tuna generates about 160 million dollars annually and provides livelihood to about 100,000 Filipinos. The processing and export of canned tuna is governed by national and international laws and regulations in order to ensure its safety. The three most common food safety issues in canned tuna are scombroid fish poisoning due to scombrotoxin or histamine formation, food borne botulism caused by the bacterial pathogen Clostridium botulinum, and contamination with potentially toxic chemicals such as lead, cadmium and mercury. In the Philippine canned tuna industry, these food safety issues are being addressed through the HACCP. The Bureau of Fisheries and Aquatic Resources (BFAR), by virtue of RA 8550 and the EC Directive 95/190/EEC, is the government agency that is accredited to provide HACCP Certification to fish processors and exporters for the local and/or international distribution of their products. Since 1995, the number of HACCP certified plants have been increasing, particularly in the Mindanao area. From 2000-2003, the total number of HACCP-certified plants increased by 7 percent. Apart from HACCP certification, BFAR also conducts accreditation for fish processing facilities, regulatory assessments of fish processing plants, certification on GMP compliance, training for industry and government inspectors and technical assistance services. From 2001-July 2003, the number of government regulatory officers and industry personnel who attended HACCP-related training courses conducted by BFAR totaled 114 and 915, respectively. In the 4 tuna canneries visited, GMP and SSOP appeared to be properly implemented. With GMP and SSOP efficiently in place, HACCP implementation is an easier task. Thus HACCP implementation in the 4 tuna canneries mostly just involved monitoring and recording-making sure that the critical limits at every critical control point (CCP) are not being exceeded. A closer look at the HACCP Plans of each cannery revealed that the content was basically the same across the 5 tuna canneries due to the more or less standardized production process for canned tuna. However, the number of identified CCP's varied from 1-5. Factors that account for these differences included : sophistication of processing equipment, historical data on the efficiency of the production process, and the additional requirements of the FSIS, the exporting country or the foreign buyer. On the other hand, common CCP's included : fish receiving/unloading, seaming and retorting, which are done to address the 3 most common food safety issues in canned tuna. A whole gamut of monitoring techniques was being used to ensure the safety of canned tuna : time-temperature monitoring, backbone temperature monitoring, sensory evaluation, histamine analysis, and cut-out tests, to name a few. Periodic HACCP Plan reviews and HACCP Audits were also being conducted to validate the effectiveness and efficiency of HACCP implementation. Apart from these, members of the HACCP team undergo HACCP-related seminars and trainings to develop their capabilities in spearheading the implementation of HACCP. They are also required to conduct in-house seminars and trainings to echo new learning to their subordinates, particularly to those who are directly involved in HACCP such as lead persons and linemen. New hires on other hand, are oriented on HACCP and its prerequisites, particularly on the principles of proper hygiene. From the interviews with key people from the government and the tuna canning sector, some issues were raised with regards to HACCP implementation. Issues raised by BFAR included lack of trained manpower and financial resources at the national, regional and local government levels, thus the need for external financial and technical assistance, limited manpower, lack of communication and transport services to support inspection activities, and the increasingly stringent requirements of fish importing countries. From the tuna canners, issues raised included limited technical qualification of the some HACCP team members to fully understand the principles of HACCP and the significance of its implementation, lack of Food Technologists in the HACCP Team, as well as in the Quality Assurance Team, limited financial capabilities to upgrade facilities and equipment, the constant need to remind some people to practice proper hygiene, and similar to BFAR, the increasingly stringent requirements of some of their export buyers. The information gathered from the experience of the tuna canneries in General Santos City with regards to HACCP implementation could help processors and exporters from the fishery sector, which are not yet HACCP-certified, develop strategies for HACCP implementation. HACCP, to be an effective food safety strategy, must be implemented under the context of a Total Quality management (TQM) system. Management committment to producing quality and safe food products for its consumers is a key. Management ought to develop programs that improve the quality of its people. Continuous education and training is very important because "Quality people produce quality products." And they do not just stop there. They aim for perfection and commit themselves to continuous improvement, which is actually the essence of TQM. At the national level, government should spearhead the production of safe and quality food through effective formulation and execution of national legislations that are in harmony with international standards and legislations. Government should form effective and efficient partnerships with various academic and private institutions in the formation of a national food safety strategy as part of its commitment to the safety not only of the Filipino people but people from around the globe.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Hazard Analysis and Critical Control Point (Food safety system); Canned fish industry -- Philippines